Religiosity, Religious Fundamentalism, and Ambivalent Sexism Toward Girls and Women Among Adolescents and Young Adults Living in Germany - Hannover, Bettina; Gubernath, John; Schultze, Martin; Zander, Lysann (Frontiers in Psychology, 2018)
The New Year’s Eve 2015 mass sexual assaults in Germany led to a broader debate about whether the perpetrators, most of them self-identifying as Muslims, were encouraged to such acts by particularly sexist attitudes toward girls and women. Here, we argue that it is not the specific religious affiliation of individuals per se that predicts sexism. Rather it should be the extent to which they are involved in their religion, i.e., their religiosity and their endorsement of religious fundamentalism. In line with the theory of ambivalent sexism, we distinguish hostile and benevolent sexism, while controlling for right-wing authoritarianism and social dominance orientation. In two Pilot Studies, we explored differences in ambivalent sexism (a) between male and female individuals of Muslim faith, Christian faith, Muslim faith, Christian faith, and no religious affiliation residing in Germany, while at the same time (b) differentiating between sexism directed toward girls and sexism directed toward women. In our Main Study, we tested the interrelations between religiosity, religious fundamentalism, and ambivalent sexism in our religious subsamples of male Christians, female Christians, male Muslims, and female Muslims using a multigroup multivariate moderated mediation analysis. In all three studies, Muslims were more religious, endorsed religious fundamentalism more strongly, and held stronger benevolent sexist beliefs toward girls and women as well as stronger hostile sexist beliefs toward women than Christians and nonreligious participants. In our Main Study, with female Christians as the reference group, male Muslims’ stronger benevolent and hostile sexist beliefs toward girls were mediated by religiosity and fundamentalism. Female Muslims’ stronger endorsement of benevolent sexism toward girls could be explained by their higher level of fundamentalism. While our findings show that differences in ambivalent sexism between religious groups were partly due to different levels of religiosity and fundamentalism, they also suggest that there are factors other than those investigated in our studies responsible for male Muslims’ particularly strong sexism. We discuss specific contents of Islamic religious teachings and honor beliefs as possible causes to be investigated further in future research.